1998
DOI: 10.1146/annurev.nutr.18.1.413
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Nutrition, and Prostate Cancer

Abstract: Cancer of the prostate gland is one of the most common malignancies in affluent nations, in part due to the application of new screening and diagnostic tools. The development of life-threatening prostate cancer is the culmination of a complex series of initiation and promotional events over a period of decades and under the influence of many interacting genetic and environmental factors. A rapidly accumulating scientific literature provides compelling evidence for the hypothesis that diet and nutrition are imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(112 citation statements)
references
References 152 publications
(213 reference statements)
1
106
0
5
Order By: Relevance
“…[23][24][25][26][27][28][29] According to a recent review article by Kolonel et al, 30 however, although early epidemiologic studies implicated dietary fat as a likely causal factor for this cancer, scientific support for such an association has [31][32][33][34][35][36] Soya is a major source of the isoflavonoids, daidzein and genistein. 33 According to Griffiths et al, 34 a Japanese male consumes approximately 20 mg of isoflavones per day, whereas Western men consume less than 1 mg/day.…”
Section: Prostatic Cancermentioning
confidence: 99%
“…[23][24][25][26][27][28][29] According to a recent review article by Kolonel et al, 30 however, although early epidemiologic studies implicated dietary fat as a likely causal factor for this cancer, scientific support for such an association has [31][32][33][34][35][36] Soya is a major source of the isoflavonoids, daidzein and genistein. 33 According to Griffiths et al, 34 a Japanese male consumes approximately 20 mg of isoflavones per day, whereas Western men consume less than 1 mg/day.…”
Section: Prostatic Cancermentioning
confidence: 99%
“…6,7 The role of diet has been investigated in several epidemiologic studies, including dietary fat intake, vitamin A, carotenoids, fruits, vegetables, dairy products and soy products. 2,3,[7][8][9][10][11][12][13][14][15][16] The most consistent dietary component associated with prostate cancer risk is fat intake, 2 an association that is apparent despite differences in the quality of the study methods and assessment of dietary intake. [2][3][4]7,8,16 Recent attention has turned to a group of phytochemicals, particularly the isoflavones found in soybeans, 10,15 since Asians, with lower prostate cancer rates, have high consumption of soy products.…”
mentioning
confidence: 99%
“…Due to its lipidic nature, breast milk is a good vehicle for lycopene, solubilized in the lipid fraction, providing for lycopene intake for breastfed children. In general, lycopene is found in human milk at approximately 3.8 mg/100 g, or 10% of the serum concentrations [29,36], although a low correlation has been found between the amount of lycopene in the diet of tested mothers and concentrations in breast milk.…”
Section: Introductionmentioning
confidence: 95%
“…Koonsvitsky et al [28] reported a reduction of nearly 30% over 16 weeks in patients consuming Olestra together with lycopene, and the presence of very high levels of phytosterols in some functional foods, which have been demonstrated to reduce carotenoid absorption. Thus, consumption of lycopene and this kind of products should be separated by several hours [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation